Rinderpest a continuing risk - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Rinderpest has been confirmed in cattle near the Ngorongoro Crater and the neighboring Serengeti National Park in northern Tanzania. The disease was diagnosed in buffalo and kudu in the Nairobi National Park last October and is thought to have...